Working time in the EU and other global economies - Demetriades, Stavroula; Pedersini, Roberto (Luxembourg, 2009)
"Globalisation is having a profound impact on economies and industrial relations systems all around the world. In the context of global competition, it is increasingly relevant to look at Europe's economic development in a wider perspective. This report explores the main industrial relations developments in the European Union, Japan and the US in the period 2006-2007. It charts the similarities and trends in industrial relations as well as the differences in basic structures and developments between these three major economies."